2005
DOI: 10.1136/ard.2004.026831
|View full text |Cite
|
Sign up to set email alerts
|

A family based study shows no association between rheumatoid arthritis and the PADI4 gene in a white French population

Abstract: BACKGROUND: Autoantibodies to citrullinated proteins (ACPA) are considered a specific marker for rheumatoid arthritis. Peptidylarginine deiminase (PAD) is the enzyme that converts arginyl into citrullyl residues; different isoforms of the enzyme are expressed in mammals. It has been suggested that the PADI4 gene may contribute to genetic susceptibility to rheumatoid arthritis, but conflicting results have been obtained in different populations. OBJECTIVE: To test the hypothesis that the PADI4 gene may con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
3
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 44 publications
(34 reference statements)
1
58
3
1
Order By: Relevance
“…However, the association between functional haplotypes of PADI4 and RA remains controversial (40,(51)(52)(53). Furthermore, in contrast to PAD-2, the PAD-4 protein was extensively distributed throughout RA synovium, did not colocalize selectively with intracellular citrullinated proteins, and was also found in OA synovium (54).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between functional haplotypes of PADI4 and RA remains controversial (40,(51)(52)(53). Furthermore, in contrast to PAD-2, the PAD-4 protein was extensively distributed throughout RA synovium, did not colocalize selectively with intracellular citrullinated proteins, and was also found in OA synovium (54).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to haplotypes of PADI4 (GenBank accession number: NT_030584), three single nucleotide polymorphisms (SNPs), padi4_92, padi4_96, and padi4_102, were selected and analyzed, as reported by Caponi et al (19). Subsequently, haplotypes were determined to be based on combinations of their three SNPs (10), as shown in Tables 2 and 3, because SNPs in PADI4 lie in a strong linkage disequilibrium block.…”
Section: The Source Of Polymorphisms Studiedmentioning
confidence: 99%
“…The three SNPs, padi4_92, padi4_96, and padi4_102, were detected by the polymerase chain 5'-AGGGTTTCGGCAGCTGTGCC-3' for padi4_102 (19), and 1 U Taq DNA polymerase (Invitrogen Co., Carlsbad, CA). The amplification protocol comprised initial denaturation at 94°C for 5 min, followed by 35 cycles of denaturation at 94°C for 30 sec, annealing at 60°C for padi4_92, at 52°C for padi4_96, and at 68°C for padi4_102 for 30 sec, extension at 72°C for 30 sec, and final extension at 72°C for 5 min.…”
Section: Determination Of Three Snps In Padi4mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Examples are a PTPN22-R620W polymorphism which is strongly associated with RA and other autoimmune diseases in Caucasian populations, but is absent in Orientals, and an association with PADI4 SNP found in Japanese populations which is not detected in most Caucasian populations, despite the presence of these gene polymorphisms. [15][16][17][18][19][20] Our own studies of the Cree/Ojibway population in Central Canada have suggested a 2-3% prevalence rate of diagnosed RA, and a 60-70% frequency of SE alleles in the background population. 7,8,21 We sought to determine additional non-HLA genes that may contribute to the high frequency of RA detected in this population.…”
Section: Introductionmentioning
confidence: 98%